The effects of Pyrus Biossieriana Bushe leaf extract on the (Kurdistan University of Medical Sciences, 2015)
Background and Aim: The Pyrus Biossieriana Bushe tree (Telka) belongs to pyrus genus and is found in northern Iran. The leaves of this tree are rich in arbutin and are used for alleviating inflammation, urinary frequency, hypertension, and hyperglycemia. In this study, we first determined the toxic dose of the Telka leaf extract and then assessed its preventive effects on the viability of HeLa cells exposed to tert-butyl hydroperoxide. Materials and: This was an experimental study. HeLa cells were cultured under standard conditions in the medium culture of RPMI 1640 in 24-well plates. Then, the Telka leaf extract was added to the medium culture and cytotoxicity of the extract was evaluated 24 hours later by using the MTT technique. Thereafter, 100, 150, 200, and 250 micromolar concentrations of tert-butyl hydroperoxide were added to the medium culture and the preventive antioxidant effects of the extract were assessed. The viability of HeLa cells and the antioxidative effects of the Telka leaf extract were evaluated by using respectively the MTT and the Ferric Reducing Antioxidant Power techniques. Mean and standard error of mean measures (Mean±SEM) were used for reporting the study results. The level of significance was set at below 0.05. Findings: Study findings revealed that the Telka leaf extract is cytotoxic at doses of 2% and higher. The differences between the less-than-2% doses of the extract and the control group were not statistically significant. The antioxidative power of the control group significantly differed from the "Telka leaf extract + tert-butyl hydroperoxide" group (P value = 0.001). After adding tert-butyl hydroperoxide, the Ferric Reducing Antioxidant Power was significantly reduced compared with the control group. Conclusion: Pre-incubation of cells at different doses of the Telka leaf extract increases the total antioxidative activity of the medium culture. Consequently, this extract can be used as a natural antioxidant.